2001
DOI: 10.1034/j.1600-0714.2001.030008489.x
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophilic nucleolar organizer regions (AgNORs) in odontogenic myxoma (OM) and ameloblastic fibroma (AF)

Abstract: Ten cases of odontogenic myxoma (OM) and six cases of ameloblastic fibroma (AF) were subjected to comparative analysis by the AgNOR technique, in order to determine a possible difference in cell proliferation index between these lesions. The mean AgNOR number of the mesenchymal component of AF was compared with its epithelial component and the difference was not found to be statistically significant. The mean AgNOR index of the AF group was significantly higher than that of the OM group. Moreover, the mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The AgNORs count in ameloblastic carcinoma was twice the count in ameloblastoma (Figs. 4,5). The NORs counted in ameloblastoma was 168 in 100 cells and in ameloblastic carcinoma, the count was 342 in 100 cells.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The AgNORs count in ameloblastic carcinoma was twice the count in ameloblastoma (Figs. 4,5). The NORs counted in ameloblastoma was 168 in 100 cells and in ameloblastic carcinoma, the count was 342 in 100 cells.…”
Section: Case Reportmentioning
confidence: 99%
“…Some researchers have suggested that the use of special stains such as Silver staining nucleolar organizer regions may be used to differentiate between various odontogenic cysts and tumors [5][6][7]. Recent research works utilizing immunohistochemical methods targeting different tissue markers have suggested a variation in expression patterns of these markers in ameloblastoma and ameloblastic carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors report that the risk of recurrence is greater as the myxoma is not encapsulated and its myxomatous tissue infiltrates the surrounding bony tissue without causing immediate destruction than to the cell proliferative index which was relatively low [22,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic reconstruction in maxillary lesions is highly advisable due to low postoperative morbidity and almost immediate phonetic and masticatory function. Furthermore prosthetic reconstruction by an obturator allows direct visualization of the primary site for recurrence detection [25].…”
Section: Introductionmentioning
confidence: 99%
“…The NOR are associated with acidic argyrophilic non-histonic proteins which can be viewed through the AgNOR technique 20,24 . Studies have applied this technique as a useful method to evaluate the differences among cellular proliferation indexes in non-neoplastic reactive lesions, as well as in benign or malignant neoplasms 3,9,15,17,23 .…”
Section: Introductionmentioning
confidence: 99%